2007
DOI: 10.1002/da.20192
|View full text |Cite
|
Sign up to set email alerts
|

Depressive, anxiety, and somatoform disorders in primary care: prevalence and recognition

Abstract: Recent studies emphasize the negative impact of comorbidity on the course of depression. If undiagnosed, depression and comorbidity contribute to high medical utilization. We aimed to assess (1) prevalences of depression alone and with comorbidity (anxiety/somatoform disorders) in primary care, (2) coexistence of anxiety/somatoform disorders in depressive patients, and (3) diagnostic validity of two screeners regarding depression with versus without comorbidity. We examined 394 primary care outpatients using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
87
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 41 publications
(40 reference statements)
8
87
0
10
Order By: Relevance
“…The rate was lower than that reported in Riyadh (18.8%) and Kuwait (20.5%) [12,13] and higher than in Qatar (13.5%, 2010). [14] Similar studies conducted in European countries revealed a prevalence rate ranging from 16.5% to 22.8%, [15][16][17] indicating that the rates in Gulf Region are comparable with those of Europe.…”
Section: Discussionmentioning
confidence: 68%
“…The rate was lower than that reported in Riyadh (18.8%) and Kuwait (20.5%) [12,13] and higher than in Qatar (13.5%, 2010). [14] Similar studies conducted in European countries revealed a prevalence rate ranging from 16.5% to 22.8%, [15][16][17] indicating that the rates in Gulf Region are comparable with those of Europe.…”
Section: Discussionmentioning
confidence: 68%
“…2 Further, a high comorbidity odds ratio (6.25) between depressive and anxiety disorders was found, leading to the conclusion that depression and anxiety comorbidity occurs more often than expected. 2 For this reason, it is important to assess both depression and anxiety, disorders or symptoms, in tandem. Diagnosis of depression and anxiety disorders is typically conducted through structured interviews based on the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV).…”
Section: Introductionmentioning
confidence: 94%
“…Despite a conceptual distinction between depression and anxiety, clinically differentiating the two constructs has proven difficult, as people who experience anxiety are often depressed as well. 1,2 In a sample of 394 primary care patients, Mergl et al (2007) found that depression without comorbidity occurred significantly less than expected by chance. 2 Further, a high comorbidity odds ratio (6.25) between depressive and anxiety disorders was found, leading to the conclusion that depression and anxiety comorbidity occurs more often than expected.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As far as it is possible to discern from an online search of the Web of Science using ' GHQ' and 'Mokken ' as search terms and no date restrictions, the GHQ, which is strong psychometrically, has not been subjected to analysis for a hierarchy among its items, although it has been used to validate other scales that have been developed using this procedure (Barkow et al 2001 ;Mergl et al 2007). One hierarchical scale for general health has been developed but does not seem to be widely used (Moorer & Suurmeijer, 1994 ;Moorer et al 2001).…”
Section: Introductionmentioning
confidence: 99%